Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume-II Government of Manipur - Planning Commission (Planning Commission, 1985)
The objective is to re-organise and strengthen permanently the capability of the existing research station at Wangbal and to establish new stations to conduct location - specific production - oriented research in the agro-climatic zones identified in their service area with special emphasis on rainfed food grains and oil seeds, non-water intensive proposals neglected crops, etc.
Government of Manipur, Planning Department